Factor V Leiden and venous thrombosis: First case report from Iraq - AL-Allawi, Nasir; Hilmi, Ferial; Jubrael, Jaladet M.S.; Al-Ameri, Ali M. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Factor V Leiden mutation is the most common cause of hereditary thrombophilia . this mutation was found to be highly prevalent in the Eastern Mediterranean region , with recently reported prevalence of 3% in random Iraqi blood donors. Aim of study: to document the case reports of factor V leiden in association with venous thrombosis in Iraqi patients. Sub. & Methods: Six patients with Doppler confirmed Deep Venous thrombosis attending the Medical City Hospital were evaluated haemostatically and by PCR for the presence of factor Vleiden mutation. The patients had ages ranging between 22-60 years , and included 5 females and one male. Results: Four were found to be heterozygous, while two were homozygous for this mutation by the DNA studies . the report includes a review of the relevant literature,and outlines the consensus opinion on indications of factor V leiden testing , and on the management of factor V Leiden associated Venous thombosis. Conclution: All the cases in this report should have been routinely tested intinially for the factor V leiden mutation , & five out of them would be eligible candidates for long term or indefinite anticoagulation, with possible reduction in morbidity & recurrence risks.